2020
DOI: 10.4103/jfmpc.jfmpc_158_20
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of awareness and practices regarding animal bites in rural community, North India

Abstract: Introduction: Repeated epidemiological studies to monitor trends of knowledge and practices are needed to guide strategies to control rabies. We conducted a study to assess the current knowledge, attitudes, and practices in relation to animal bites in the rural area of north India. Methods: House to house survey to collect data on animal bites was conducted among 300 households (assuming awareness regarding animal bites to be 25%, precision 95%, and power of 80%) from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…4 Majority of animals in our study (70.4%) were stray and wild animals which is almost similar to a study conducted by Umarigar et al in 2012 where 94% of cases were bitten by stray dogs but in a study conducted by Singh et al in 2020, bites by pet animals (47%) are more common than those by stray animals (35.9%), followed by wild animals (12.8%). 12,13 We have found the most common site of animal bite was lower limb (53.6%) which is almost same like the study conducted by Sangeetha et al in 2016,where also the majority had animal bites were on leg (60.87%). 9 The lower limb is the most common area in our study may be because in tribal area majority of male people wear lungi, gamcha or dhoti.…”
Section: Discussionsupporting
confidence: 84%
“…4 Majority of animals in our study (70.4%) were stray and wild animals which is almost similar to a study conducted by Umarigar et al in 2012 where 94% of cases were bitten by stray dogs but in a study conducted by Singh et al in 2020, bites by pet animals (47%) are more common than those by stray animals (35.9%), followed by wild animals (12.8%). 12,13 We have found the most common site of animal bite was lower limb (53.6%) which is almost same like the study conducted by Sangeetha et al in 2016,where also the majority had animal bites were on leg (60.87%). 9 The lower limb is the most common area in our study may be because in tribal area majority of male people wear lungi, gamcha or dhoti.…”
Section: Discussionsupporting
confidence: 84%
“…Fourteen sources described drivers of rabies related to lack of awareness and understanding of the disease, its causes and prevention. Communities often reported low awareness of rabies, in terms of preventing bites and behaviour following a bite or other contact with potentially infected animals [ 28 , 29 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] ]. Some sources discussed community beliefs and the use of traditional medicines as prevention or post-exposure prophylaxis [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some sources discussed community beliefs and the use of traditional medicines as prevention or post-exposure prophylaxis [ 29 ]. Studies in India found some participants had heard about rabies, but knowledge of first-aid following a bite was poor, with application of chillies, turmeric or kerosene and visiting traditional healers recommended [ 33 , 35 , 37 ]. In two Pakistan studies, most participants stated there had been no rabies awareness campaign in their community [ 28 , 38 ], with similar findings in India [ 32 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, crucial information about the disease eludes the most vulnerable populations, such as school-age children, families with children less than 14 years of age and religious groups that support FRD in the human settlements (Madjadinan et al 2020;Tiwari et al 2019a). Besides the lack of knowledge about the disease, misplaced attitudes of the communities in endemic countries persist regarding post-bite management of wounds, such as applying traditional therapies and belief in local priests to provide relief through religious rituals (Singh et al 2020;Jemberu et al 2013). Another cause of concern is a lack of knowledge about rabies and post-bite management of wounds by the frontline medical staff.…”
Section: (A) Knowledge Attitudes and Practicesmentioning
confidence: 99%